2015
DOI: 10.1097/phh.0000000000000087
|View full text |Cite
|
Sign up to set email alerts
|

The Proof's in the Partnerships

Abstract: The strengthened requirement for nonprofit hospitals to complete a community health needs assessment and implementation plan in the Affordable Care Act, concurrent with a new voluntary accreditation process for local health departments that requires collaborative community health assessments and community health improvement plans, have led to a resurgence of interest in assessment and improvement planning. This study provides baseline data that will help determine whether the Affordable Care Act and public hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…In a statewide analysis in Missouri, Beatty, Wilson, and colleagues found significant variation in cooperation and no strong predictors of collaboration between the non-profit hospital and other organizations (22,62). Laymon et al provided baseline data from the first CHNA cycle in 2013 and reported that 53% of LHDs collaborated with hospitals on needs assessments, with likelihood increasing in areas of large populations (63). In a case study, Sampson, Gearon and Boe describe a process wherein a hospital-LHD partnership drew upon the local health department's long history of community collaboration and engaged 1,800 Polk County, WI residents in developing the CHNA, many of whom continue to be involved in workgroups to address the identified needs (64).…”
Section: Key Conclusion Related To Community Benefitmentioning
confidence: 99%
“…In a statewide analysis in Missouri, Beatty, Wilson, and colleagues found significant variation in cooperation and no strong predictors of collaboration between the non-profit hospital and other organizations (22,62). Laymon et al provided baseline data from the first CHNA cycle in 2013 and reported that 53% of LHDs collaborated with hospitals on needs assessments, with likelihood increasing in areas of large populations (63). In a case study, Sampson, Gearon and Boe describe a process wherein a hospital-LHD partnership drew upon the local health department's long history of community collaboration and engaged 1,800 Polk County, WI residents in developing the CHNA, many of whom continue to be involved in workgroups to address the identified needs (64).…”
Section: Key Conclusion Related To Community Benefitmentioning
confidence: 99%
“…While there were early models of hospital partnerships with community-based organizations (Bucks County Health Improvement Partnership, n.d.; Prybil et al, 2014) to address community health, these efforts have more recently been embraced as a strategy to support health systems’ population health management activities (Berwick et al, 2008; Institute for Healthcare Improvement, 2018). Some examples of these types of partnerships include hospital–public health partnerships for CHNAs (Hogg et al, 2015; Laymon et al, 2015; Singh & Carlton, 2017; Wilson et al, 2014), multisector collaborative networks (Hogg & Varda, 2016; Mays et al, 2016; Towe et al, 2016), and partnerships with community-based organizations to improve access to community resources (Lindau et al, 2016; Morgan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This concept can be seen in many efforts aimed at multi-sector collaboration in public health, health care delivery organizations, community-based organizations, and the private sector. These include such varied activities as health department accreditation [11], the Robert Wood Johnson Foundation’s Culture of Health initiative [1], the Health in All Policies (HiAP) approach [12], and the San Francisco Federal Reserve Bank’s Pathways to System Change initiative [13]. Despite their varied rationale and organizational forms, the key elements of these initiatives are well described by Kania and Kramer’s Collective Impact framework [4], which includes: 1) a common agenda, 2) shared measurement systems, 3) mutually reinforcing activities, continuous communication, and a backbone support organization.…”
Section: Introductionmentioning
confidence: 99%